A new on-line technique to identify fault location within long transmission lines. (November 2019) - Abu-Siada, A.; Mir, Saif
Abstract: Identification of fault location within transmission lines is essential in order to restore service rapidly, reduce unplanned outage time, minimise revenue loss, and improve network reliability. Several transmission line fault-locating techniques based on travelling waves, apparent impedance and direct circuit analysis have been introduced in the literatures. However, these methods are either impractical or too expensive to implement. In this paper, a new online technique is introduced to accurately detect the fault location within transmission lines. The technique relies on constructing a voltage-current ( V-I ) locus diagram that could be measured at every power frequency cycle to provide up-to-date condition state of the line. The technique does not call for special equipment as it utilises the existing metering or protection devices connected to the sending and receiving ends of the transmission line to monitor the voltage and current at both ends. To assess the robustness of the proposed technique, various types of faults have been simulated on transmission lines of various lengths and voltage levels using DIgSILENT PowerFactory software. Variations in load conditions, effect of fault resistance, different line configurations are also investigated. Results reveal the ability of the proposed technique to detect fault locations in transmission lines with high accuracy. In contrary with existing fault-locating techniques that are only employed to identify the location of faults after their occurrence, the proposed technique has the potential to detect high impedance faults. Thus an early warning signal can be issued to avoid any catastrophic consequences. The proposed technique is cost effective and easy to implement for new and existing transmission line installations. Highlights: New online technique to detect the fault location within transmission lines. The technique relies on simple voltage-current measurements at both ends of line. The technique does not need special equipment as it utilises the existing devices. The technique can detect high impedance faults to avoid catastrophic consequences.